FECOLSOG: Improving maternal, sexual and reproductive health - Díaz-Yamal, Ivonne (Revista Colombiana de Obstetricia y Ginecología, 2016)
Under the leadership of its Board of Directors, the Colombian Federation of Obstetrics and Gynaecology (FECOLSOG) has undertaken the task of developing a strategic plan looking to 2020. This new plan seeks to respond to the health situation in our country and it focuses on public health actions designed to improve maternal and perinatal indicators, develop interventions in sexual and reproductive health, work on training and recertification of our members, and update procedures that need to be covered by benefit plans paid through public funds.